Identification of farms of essence and size - Макаренко Ю. П., Ю. П. (Scientific Progress & Innovations, 2012)
Essence of farms and their identity is certain to the peasant economies after the signs of production units, will hire workers, to the level of marketability, «peasant» and «farmer». Authentication of farms is set after criteria: proprietor of farm, management and production process, integration with other forms of management, control functions after a production, sizes of enterprise. Small agrarian enterprises are differentiated after the sizes of land-tenure on the personal peasant, domestic and farmer.